Answer:
see explanation
Step-by-step explanation:
(a)
A recursive formula allows any term in the sequence to be found by adding the common difference d to the previous term.
Here d = - 4 , then recursive formula is
=
- 4 with a₁ = 2
(b)
The explicit formula for an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = 2 and d = - 4, thus
= 2 - 4(n - 1) = 2 - 4n + 4 = 6 - 4n ← explicit formula
(c)
Using the recursive formula
a₁ = 2
a₂ = 2 - 4 = - 2
a₃ = - 2 - 4 = - 6
Using the explicit formula
a₅ = 6 - 4(5) = 6 - 20 = - 14
a₁₀ = 6 - 4(10) = 6 - 40 = - 34
a₁₀₀ = 6 - 4(100) = 6 - 400 = - 394
Answer:
that is crazy i have not idea what the answer is
Step-by-step explanation:
You multiply 3x - y = 3.
So then it's:
6x - 2y = 3
-2x + 2y =6
which equals 4x = 9
Answer:
Step-by-step explanation:
N(17+x)=34x−r
17n+xn=34x-r
xn= 34x - r - 17n
xn-34x= -r - 17n
x(n-34)= -r - 17n
x= (-r - 17n)/(n-34)
Answer:

Step-by-step explanation:
